2019
DOI: 10.1002/jcp.28326
|View full text |Cite|
|
Sign up to set email alerts
|

Retracted: Icariin attenuates methotrexate chemotherapy‐induced bone marrow microvascular damage and bone loss in rats

Abstract: Methotrexate (MTX), a widely used antimetabolite in paediatric cancer to treatment, has been widely reported to cause bone loss and bone marrow (BM) microvascular (particularly sinusoids) damage. Investigations must now investigate how MTX‐induced bone loss and microvasculature damage can be attenuated/prevented. In the present study, we examined the potency of icariin, an herbal flavonoid, in reducing bone loss and the dilation/damage of BM sinusoids in rats caused by MTX treatment. Groups of young rats were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 49 publications
0
4
0
Order By: Relevance
“…Interestingly, Jiang et al demonstrated that icariin significantly enhanced the chemosensitivity of cisplatin-resistant ovarian cancer cells by suppressing autophagy [31]. Moreover, icariin could effectively attenuate paclitaxel-induced neuropathic pain [32] and chemotherapy-induced bone marrow microvascular damage [33]. Based on these evidences, we thus speculated that icariin might play an important role in TAM resistance.…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, Jiang et al demonstrated that icariin significantly enhanced the chemosensitivity of cisplatin-resistant ovarian cancer cells by suppressing autophagy [31]. Moreover, icariin could effectively attenuate paclitaxel-induced neuropathic pain [32] and chemotherapy-induced bone marrow microvascular damage [33]. Based on these evidences, we thus speculated that icariin might play an important role in TAM resistance.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, as CXCL12 exerts biological effects through binding with receptor CXCR4, future studies are required to further investigate the potential roles of CXCL12‐CXCR4 axis in MTX and/or DEX treatment‐associated growth plate cartilage resorption and thinning and the potential therapeutic effect with administration of a CXCR4 inhibitor as used in a rodent bone cancer‐induced bone lysis model (Diamond et al, 2009). Furthermore, while previous studies have demonstrated that cancer chemotherapy including MTX chemotherapy can cause significant damage to the bone marrow microvascular system accompanying the aggravated bone loss (Hassanshahi et al, 2017; Hassanshahi et al, 2019a; 2019b; 2019c), further studies are required to clarify any possible effects of MTX and DEX treatments on vasculogenesis and/or angiogenesis at the growth plate/metaphysis junction. This is important as vasculogenesis and/or angiogenesis are crucial for remodelling calcified hypertrophic growth plate cartilage into woven bone (primary spongiosa) and thus for the coupling of cartilage scaffold production and new endochondral bone formation during bone growth (Gerber et al, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…demonstrated that oral ICA treatment prevents bone loss in iron-overloaded mice and inhibited the differentiation and function of osteoclasts. In addition, ICA reduces bone loss induced by methotrexate chemotherapy in rats ( 23 ). As these studies demonstrate the osteoporosis-related activity of ICA, it was hypothesized that ICA may exert a protective effect on TAA-induced bone loss.…”
Section: Introductionmentioning
confidence: 99%